2017
DOI: 10.3389/fpsyg.2017.00713
|View full text |Cite
|
Sign up to set email alerts
|

Does a Flatter General Gradient of Visual Attention Explain Peripheral Advantages and Central Deficits in Deaf Adults?

Abstract: Individuals deaf from early age often outperform hearing individuals in the visual periphery on attention-dependent dorsal stream tasks (e.g., spatial localization or movement detection), but sometimes show central visual attention deficits, usually on ventral stream object identification tasks. It has been proposed that early deafness adaptively redirects attentional resources from central to peripheral vision to monitor extrapersonal space in the absence of auditory cues, producing a more evenly distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 52 publications
(154 reference statements)
1
10
0
Order By: Relevance
“…Although many studies show no perceptual differences between deaf and hearing adults within the central visual field (Bosworth and Dobkins 1999;Brozinsky and Bavelier 2004;Stevens and Neville 2006), some disadvantages have been noted in deaf adults (Proksch & Bavelier, 2002;Parasnis, Samar & Berent, 2003;Samar & Berger, 2017), possibly explained by the reduction of neural resources we find in the central visual field representations. Furthermore, there is evidence of a central/peripheral trade-off in visual attention of deaf individuals (Proksch & Bavelier, 2002;Parasnis, Samar & Berent, 2003) and responses measured in visual motion area V5/hMT+ (Bavelier et al, 2001).…”
Section: Discussionmentioning
confidence: 61%
“…Although many studies show no perceptual differences between deaf and hearing adults within the central visual field (Bosworth and Dobkins 1999;Brozinsky and Bavelier 2004;Stevens and Neville 2006), some disadvantages have been noted in deaf adults (Proksch & Bavelier, 2002;Parasnis, Samar & Berent, 2003;Samar & Berger, 2017), possibly explained by the reduction of neural resources we find in the central visual field representations. Furthermore, there is evidence of a central/peripheral trade-off in visual attention of deaf individuals (Proksch & Bavelier, 2002;Parasnis, Samar & Berent, 2003) and responses measured in visual motion area V5/hMT+ (Bavelier et al, 2001).…”
Section: Discussionmentioning
confidence: 61%
“…Enhanced peripheral visual sensitivity is reported in deaf cats [3] and adult humans [1,2,13], particularly in the far peripheral visual field [4,5]. Although many studies show no perceptual differences within the central visual field between deaf and hearing adults [1,14], evidence of a central/peripheral trade-off has been reported in deaf adults for some tasks [15,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, detection of changes outside foveal vision seems to be faster in deaf than in hearing individuals (Loke and Song, 1991;Chen et al, 2006;Dye et al, 2009), suggesting that stimuli outside the fovea are more likely to challenge attentional control in deaf populations, at least when those stimuli are of relevance to solving the task (Bavelier et al, 2006;Belanger and Rayner, 2015). For the ventral stream, Armstrong et al (2002) showed no effect of deafness, whereas others showed altered effects of deafness in both ventral and dorsal streams (Weisberg et al, 2012;Samar and Berger, 2017). Because the dorsal stream is susceptible to effects of deafness, with increased attentional resources used for processing of stimuli in the periphery, deaf individuals might perform worse than hearing individuals on visual tasks where stimuli outside the fovea need to be suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…In other trials, flanking stimuli are congruent with the target stimulus, which leads to faster responses. The difference in response times between incongruent and congruent trials is an indicator of visuospatial attentional control (Rueda et al, 2004), and with an increase in attentional allocation to stimuli outside the fovea in deaf individuals (Bavelier et al, 2006) as well as altered ventral stream processing (Weisberg et al, 2012;Samar and Berger, 2017), an incongruence effect is likely to be stronger for deaf compared to hearing individuals. Thus, despite superior performance on some tasks related to the dorsal stream, deaf individuals are more distracted by flanking stimuli in a Flanker task than hearing participants (Dye et al, 2007;Dye and Hauser, 2014), irrespective of sign language skill (Proksch and Bavelier, 2002;Dye et al, 2007; also see Bosworth and Dobkins, 2002;Dye et al, 2009).…”
Section: Introductionmentioning
confidence: 99%